Leachate Treatment Using Up-Flow Anaerobic Sludge Blanket System - Ridzuan, Mohd Baharudin; Daud, Zawawi; Ahmad, Zulkifli; Abd Latiff, Ab Aziz; Awang, Halizah (International Journal of Integrated Engineering, 2018)
Leachate is one of the major problems to overcome in managing the landfill. Low cost treatment, less maintenance and environmental friendly are considered as the best practices to treat leachate. Without a proper treatment, leachate could give a negative effect to the environment and become a pollutant. This research focused on the effectiveness of Up-flow Anaerobic Sludge Blanket on leachate treatment using reactor tank in lab-scale. The effectiveness of this system was evaluated by comparing the percentage of nutrient removal. Moreover, leachate characteristic was conducted to determine the nutrient content. Five (5) main parameters were selected to be monitored which are Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), Total Nitrogen (TN) and Total Phosphorus (TP). Experiments were run for 30 days and Â the readings were recorded every 3 days. Results show that the capability of UASB in the removal several parameters. This UASB had a greater ability in removal of Total Phosphorus and TSS with 89% and 81% average removal each. COD removal shows encouraging removal graph more than 70%. While BOD, 64% and Total Nitrogen as 50%. Results showed that UASB system was capable to remove major pollutants from landfill leachate.